Revitalizing the Islamic Religious Education Curriculum in Higher Education: Integrating Ecotheology and Social Justice to Support the Sustainable Development Goals (SDGs) - Alwazir Abdusshomad (Prodi Pendidikan Agama Islam FTIK IAIN Palopo, 2026)
The implementation of the Sustainable Development Goals (SDGs) in Indonesian higher education has largely emphasized environmental and social dimensions, while ethical and spiritual aspects remain relatively overlooked. This study positions Islamic Education (PAI) as a vital instrument to address this moral gap through a transformative education approach. This article aims to formulate a conceptual framework for integrating Islamic values rooted in ecotheology and social justice into the PAI curriculum to strengthen the achievement of the SDGs agenda, particularly SDG 4 (Quality Education), SDG 12 (Responsible Consumption and Production), SDG 13 (Climate Action), and SDG 16 (Peace, Justice, and Strong Institutions). The study employs a systematic literature review combined with a critical analysis of 45 reputable academic publications from 2020–2025. The findings highlight three key pillars: Tauhid as the basis of an ecological paradigm, Khilafah as an ethical mandate of stewardship, and Maqasid al-Shari’ah as a socio-ecological justice framework. Theoretically, this study offers a new pedagogical model that shifts PAI from mere normative knowledge transfer to action-based education aligned with global sustainability concerns